Gelatin as Biomaterial for Tissue Engineering - Echave, M.; Burgo, L.; Pedraz, J.; Orive, G.
Tissue engineering is considered one of the most important therapeutic strategies of regenerative medicine. The main objective of these new technologies is the development of substitutes made with biomaterials that are able to heal, repair or regenerate injured or diseased tissues and organs. These constructs seek to unlock the limited ability of human tissues and organs to regenerate. In this review, we highlight the convenient intrinsic properties of gelatin for the design and development of advanced systems for tissue engineering. Gelatin is a natural origin protein derived from collagen hydrolysis. We outline herein a state of the art of gelatin-based composites in order to overcome limitations of this polymeric material and modulate the properties of the formulations. Control release of bioactive molecules, formulations with conductive properties or systems with improved mechanical properties can be obtained using gelatin composites. Many studies have found that the use of calcium phosphate ceramics and diverse synthetic polymers in combination with gelatin improve the mechanical properties of the structures. On the other hand, polyaniline and carbon-based nanosubstrates are interesting molecules to provide gelatin-based systems with conductive properties, especially for cardiac and nerve tissue engineering. Finally, this review provides an overview of the different types of gelatin-based structures including nanoparticles, microparticles, 3D scaffolds, electrospun nanofibers and in situ gelling formulations. Thanks to the significant progress that has already been made, along with others that will be achieved in a near future, the safe and effective clinical implementation of gelatin-based products is expected to accelerate and expand shortly.
Keywords: 3D SCAFFOLDS; BIOMATERIAL; BONE; GELATIN; PARTICLES; REGENERATIVE MEDICINE; TISSUE ENGINEERING